Predictors of diabetes‐related distress before and after FreeStyle Libre‐1 use: Lessons from the Association of British Clinical Diabetologists nationwide study. Issue 10 (29th June 2021) - Deshmukh, Harshal; Wilmot, Emma G.; Gregory, Robert; Barnes, Dennis; Narendran, Parth; Saunders, Simon; Furlong, Niall; Kamaruddin, Shafie; Banatwalla, Rumaisa; Herring, Roselle; Kilvert, Anne; Patmore, Jane; et al.
Abstract: Aim: To identify the baseline demographic and clinical characteristics associated with diabetes‐related distress (DRD) and factors associated with improvement in DRD after initiating use of the FreeStyle Libre (FSL) in people living with type 1 diabetes (T1D). Methods: The study was performed using baseline and follow‐up data from the Association of British Clinical Diabetologists nationwide audit of people with diabetes who initiated use of the FSL in the United Kingdom. DRD was assessed using the two‐item diabetes‐related distress scale (DDS; defined as the average of the two‐item score ≥3). People living with T1D were categorized into two groups: those with high DRD, defined as an average DDS score ≥3 and those with lower DRD, defined as a DDS score <3. We used a gradient‐boosting machine‐learning (GBM) model to identify the relative influence (RI) of baseline variables on average DDS score. Results: The study population consisted of 9159 patients, 96.6% of whom had T1D. The median (interquartile range [IQR]) age was 45.1 (32‐56) years, 50.1% were women, the median (IQR) baseline body mass index was 26.1 (23.2‐29.6) kg/m 2 and the median (IQR) duration of diabetes was 20 (11‐32) years. The two components of the DDS were significantly correlated (r 2  = 0.73; P  < 0.0001). Higher DRD was prevalent in 53% (4879/9159) of people living with T1D at baseline. In the GBM model, the top baseline variables associated with average DDS score were baseline glycated haemoglobin (HbA1c; RI = 51.1), baseline Gold score (RI = 23.3), gender (RI = 7.05) and fear of hypoglycaemia (RI = 4.96). Follow‐up data were available for 3312 participants. The top factors associated with improvement in DDS score following use of the FSL were change in Gold score (RI = 28.2) and change in baseline HbA1c (RI = 19.3). Conclusions: In this large UK cohort of people living with T1D, diabetes distress was prevalent and associated with higher HbA1c, impaired awareness of hypoglycaemia and female gender. Improvement in glycaemic control and hypoglycaemia unawareness with the use of the FSL was associated with improvement in DRD in people living with T1D.